[tex]a^3+b^3=(a + b)(a^2 - ab + b^2)\\\\\\22222^3+ 33333^3 =(22222+33333)\cdot(22222^2-22222\cdot33333+33333^2)=\\\\55555\cdot(22222^2-22222\cdot33333+33333^2)=\\\\5\cdot11111\cdot(22222^2-22222\cdot33333+33333^2)[/tex]
Jeden z czynników jest równy 5, więc liczba jest podzielna przez 5
[tex]13^6-11^6=(13^3)^2-(11^3)^2=(13^3-11^3)(13^3+11^3)=\\\\(13^3-11^3)(13^3+11^3)=(13-11)\cdot(13^2+13\cdot11+11^2)\cdot(13+11)\cdot(13^2-13\cdot11+11^2)=\\\\2\cdot(13^2+13\cdot11+11^2)\cdot24\cdot(13^2-13\cdot11+11^2)=48\cdot(13^2+13\cdot11+11^2)\cdot(13^2-13\cdot11+11^2)[/tex]
Jeden z czynników jest równy 48, więc liczba jest podzielna przez 48